Efficacy and Safety of Elagolix 150 mg QD in Women With Uterine Fibroids and Heavy Menstrual Bleeding [A87]. (May 2022) - Kroll, Robin; Poindexter, Alfred; Ng, Juki; Li, Hong; Snabes, Michael
Abstract : INTRODUCTION: Elagolix is an oral GnRH antagonist approved in combination with hormonal add back therapy (elagolix 300 mg BID+estradiol/norethindrone acetate QD) for the treatment of heavy menstrual bleeding (HMB) associated with uterine fibroids (UF) for up to 24 months (M). However, estradiol and/or norethindrone acetate may be contraindicated in some patients with UF and HMB. METHODS: This phase 4, randomized, double-blind, placebo-controlled study evaluated the efficacy and safety of elagolix 150 mg QD for UF-associated HMB. Premenopausal women with UF and HMB were randomized 2:1 to elagolix 150 mg QD or placebo for 6M. Assessments included the proportion of patients with menstrual blood loss (MBL) volume less than 80mL at the final month (FM) and greater than or equal to 50% reduction in MBL volume from baseline to FM, and evaluating adverse events (AEs). RESULTS: Eighty-two patients were randomized (54 elagolix, 28 placebo). Elagolix 150 mg QD reduced MBL volume to less than 80mL and by greater than or equal to 50% from baseline in a clinically meaningful and statistically significantly larger proportion of patients versus placebo at FM (49.4% versus 23.3%, respectively; difference of 26.1%; P < .05). The most common AEs were headache and hot flush (13.0% and 11.1%, respectively, with elagolix; both 3.6% placebo). The safety profile was consistent with previously established elagolix 150 mg monotherapy safety. CONCLUSION: Elagolix 150 mg QD alone significantly reduced HMB in patients with UF after 6M of treatment with no new safety signals and may be an effective therapeutic option for patients with contraindications to estradiol and/or norethindrone acetate.